Abstract WP76: Leveraging Digital Health to Improve the Cardiovascular Health of Stroke Survivors: A Nurse-Led Approach - Meza Burgos, Claudia Patricia; Juega, Jesus; Francisco, Jaume; Santos, Alba; Duran, Laura; Alvarez-Sabin, Jose; SERO, LAIA; Ustrell, Xavier; Bashir, Saima; Molina, Carlos; Pagola, Jorge (Stroke (1970), 2025)
Background: The aim of this study was to determine the impact of a nurse-led digital health intervention targeting cardiovascular risk in patients with cryptogenic stroke, as well as to identify factors associated with whether or not cardiovascular health improves. Methods: This is a secondary analysis of an ongoing randomized controlled trial of an digital health intervention that integrates advanced nursing practice to improve cardiovascular health in cryptogenic stroke patients aged 55 years or older, recruited in Spain (SMART THUNDER NCT03169257). The intervention consists of using an activity tracker and a mHealth application. The follow-up period was 12 months. The Life's Simple 7 (LS7 score) is use to determine cardiovascular risk. Results: Out of 116 subjects, 59 participated in the digital health intervention group and 56 received usual care. Among all participants, higher self-reported health literacy (OR = 1.32, 95% CI: 1.166 - 1.501, p = 0.000) and higher self-reported attitude toward technology (OR = 1.26, 95% CI: 1.091 - 1.455, p = 0.002) were associated with and ideal LS7 score at 3 months. Compared with those receiving usual care, participants in the digital health intervention group showed significant improvement of LS7 score from 3 to 12 months (p = 0.013). Conclusion: The nurse-led digital health intervention was associated with greater self-improvement of cardiovascular health in stroke patients over time. This study also demonstrated that higher health literacy and a positive attitude towards technology contribute to improved cardiovascular outcomes, allowing us to identify a vulnerable subset of patients that might benefit from a more comprehensive digital health intervention.